PROJECT-BASED LEARNING IN ACHIEVING STUDENTS' RESEARCH SKILLS IN TIMES OF COVID-19 - Quincho Apumayta, Raúl (2023)
The objective of this study was to determine the influence of Project-based learning (PBL) as a learning strategy on the achievement of research competencies of students in the fifth cycle of Mathematics, Computing and Informatics Professional Career in the Faculty of Education Science at National University of Huancavelica. The scientific method, development tests and a technical report were used to obtain the results. It was found that the application of PBL had a positive and significant influence on the achievement of the research competencies of the students, who moved from the pre-formal domain level to the resolution domain, and reached the receptive domain level in terms of technological investigative competencies; However, none reached the strategic level. These findings suggest that PBL can be an effective strategy to improve learning and the achievement of research competencies in students